Study of Fatty Acids Profile in Kernel Oil of Heynea trijuga Roxb. Ex Sims. (syn. Trichilia connaroides (Wight & Arn.) Bentv.) - Ashutosh K. Mittal; Shishir Tandon (Journal of Chemistry)
Seed oils have been used for centuries by communities as food, medicine, cosmetic applications, and fuel. Recently, there has been a renewed interest in these nontimber forest products specifically for use in cosmetic formulations. The fatty acid compositions of kernel oil of Heynea trijuga was analyzed by GC-FID. The results showed that the oil content was 37.61 percent (w/w) in seed. Seed oil was rich in unsaturated fatty acids. Important fatty acids present were palmitic acid (22.12%), stearic acid (7.51%), oleic acid (25.20%), and linoleic acid (11.65%).